2000
DOI: 10.33584/jnzg.2000.62.2380
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of change in forage quality and seasonality on sheep farm profitability

Abstract: benefits of altering the quality and seasonality of pasture supply in sheep farming enterprises. Three representative regions in New Zealand were studied; winter-cold and summer-wet (e.g., Southland, Otago and Central North Island); winter-cold, summer-dry (e.g., South Island East Coast); and winter-warm, summer-dry (e.g., North Island East Coast). Two different lamb-finishing enterprises were also analysed within each region; a conventional system where the lamb supply pattern was aligned with feed av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The supply of high quality pasture is crucial for maximizing animal performance in pasture‐based ruminant production systems, with imposed grazing management decisions significantly influencing sward productivity and quality (Francis & Smetham, ; Webby & Sheath, ). Grass, either grazed or conserved, can supply up to 95% of the energy requirements of sheep (Davies & Penning, ), providing producers in temperate grazing regions an ideal opportunity to maximize output from grass through increased herbage dry‐matter (DM) production and utilization (Keady, Hanrahan, & Flanagan, ; Shalloo, Kennedy, Wallace, Rath, & Dillon, ).…”
Section: Introductionmentioning
confidence: 99%
“…The supply of high quality pasture is crucial for maximizing animal performance in pasture‐based ruminant production systems, with imposed grazing management decisions significantly influencing sward productivity and quality (Francis & Smetham, ; Webby & Sheath, ). Grass, either grazed or conserved, can supply up to 95% of the energy requirements of sheep (Davies & Penning, ), providing producers in temperate grazing regions an ideal opportunity to maximize output from grass through increased herbage dry‐matter (DM) production and utilization (Keady, Hanrahan, & Flanagan, ; Shalloo, Kennedy, Wallace, Rath, & Dillon, ).…”
Section: Introductionmentioning
confidence: 99%
“…This was driven by better feed quality increasing animal liveweight gain. Correspondingly, Webby and Sheath (2000) demonstrated that altering feed quality was a much stronger driver of farm profitability than increasing dry matter production. Higher energy content in legume-based pasture has consistently been identified as key to increased profitability (Stevens et al, 2012;Rendel et al, 2017;Stevens and Casey 2017;Moot et al, 2019).…”
Section: Whole Farm Efficiencymentioning
confidence: 99%
“…The inclusion of sociological research acknowledges that people play an extremely important part in the Field et al 1981;McCall et al 1986;Marshall et al 1991;Webby et al 1995;Rollo et al 1996;Woodward et al 2000;Ridler et al 2001;Woodward et al 2001;Rendel et al 2013;Spooner & Li 2013 Economic Beck & Dent 1987;Marshall et al 1991;Webby et al 1995;Ridler et al 2001;Rendel et al 2013 Environmental Synge et al 2013;Vogeler et al 2014White et al 2010Dynes et al 2011;Mackay et al 2012McCall 1984aMcCall 1984b;McCall et al 1986;Journeaux et al 1987;Parker et al 1992;Barker & Baars 1993;Stevens et al 2000;Webby & Sheath 2000;Murray et al 2007;White et al 2010;Dynes et al 2011;Mackay et al 2012;Beck & Dent 1987Journeaux et al 1987;Parker et al 1992;Korte & Rhodes 1993;Dake 1994;Barker et al 1999;Ormond et al 2002;Stevens et al 2000;Webby & Sheath 2000;White et al 2010;Dynes et al 2011;…”
Section: Sociology Researchmentioning
confidence: 99%